Analisis Tingkat Kepuasan Masyarakat terhadap Pelayanan pada Kantor Kecamatan Bonggakaradeng Kabupaten Tana Toraja - Ellyn Patadungan; Marniati Marniati (Journal Economic Excellence Ibnu Sina, 2024)
Abstract : Analysis of the level of community satisfaction with services at the Bonggakaradeng District Office, Tana Toraja Regency. The problem in this study is how the Level of Community Satisfaction with the Services obtained at the Bonggakaradeng District Office. This study uses a quantitative descriptive research method. The type of data used is primary data obtained through observation, questionnaire filling and documentation while secondary data is obtained from records, books and report documents related to the problem being researched. The method in this study is quantitative descriptive analysis. The results of this study show that the value of the Community Satisfaction Index (IKM) for services at the Bonggakaradeng District Office is 3,192 with a conference number of 79.8, so the service performance is in the category of good service quality. The results of the 9 indicators of the Community Satisfaction Index are as follows: (1) the service company has an IKM value of 78.18 with the good category, (2) the ease of service procedures with a value of 77.72 with the good category, (3) the speed of service time has a value of 71.35 with the poor category, (4) the service cost/tariff with a value of 100.00 with the very good category, (5) the suitability of the service product with a value of 79.09 with the good quality category, (6) the competence of the officers has a value of 78.62 with good quality, (7) the behavior of officers in providing services has a value of 77.25 with good quality, (8) the quality of infrastructure facilities has a value of 76.35 with poor quality and (9) the handling of service complaints has an IKM score of 86.8 with good quality.